Global Research and Standardization Progress of 5G - Xiaobei Chen; Kejun Wei (Dianxin kexue)
The global overall progress and trends of 5G were summarized，including the user trends，service trends in the future，5G key capabilities and the overall work plan identified by ITU and work plan of 5G in 3GPP. In addition，outcomes of EU METIS research project and research progress of NGMN were discussed. Finally，the main outcomes of IMT-2020 Promotion Group in 5G vision，scenarios，key capabilities，overall concept and core technology were introduced.